Effect of oxygen concentration and distribution on holes transfer and photoelectrocatalytic properties in hematite. (8th February 2021) - Zhou, Mengyang; Chen, Shuai; Bai, Jing; Wang, Jiachen; Zhang, Yan; Zhou, Tingsheng; Li, Jinhua; Shangguan, Wenfeng; Zhou, Baoxue
Abstract: The holes transfer efficiency is a key issue in the process of photoelectrocatalytic water splitting. Here, we found that the oxygen concentration and distribution in hematite evidently affected the bulk and surface holes transfer, and thus influenced the performance of photoelectrocatalytic water splitting. Two macro-changes on oxygen were observed during the thermal treatment. The first-stage led to a lower bulk O/Fe ratio of only 1/1 and the generation of adsorbed oxygen, obtaining porous nanorods (NRs) with a ~1.4 nm FeOx layer. Bulk charge recombination centers and surface deep traps caused a lower bulk and surface charge transfer. The second-stage led to a bulk O/Fe ratio of nearly 3/2 and single high crystallization NRs. Major increases in charge transfer constant from 0.27 to 4.5 s −1 and in photocurrent density (vs.1.23 VRHE ) from 0.0235 to 1.20 mA/cm 2 were observed, which demonstrates the higher holes transfer efficiency. Furthermore, the connection of oxygen migration and charge transfer was derived. This work could provide effective guidance for further optimization of semiconductor photoanodes. Graphical abstract: Image 1 Highlights: Oxygen-changes in hematite evidently affected photoelectrocatalytic water splitting. Two changes on oxygen concentration and distribution were observed by annealing. Oxygen deficiency of bulk was showed in first stage, causing charge recombination. Surface deep traps were formed due to excessive absorbed oxygen on the surface. High crystallization was obtained by the second stage for superior holes transfer.